2014
DOI: 10.1093/gbe/evu210
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factors Bind Negatively Selected Sites within Human mtDNA Genes

Abstract: Transcription of mitochondrial DNA (mtDNA)-encoded genes is thought to be regulated by a handful of dedicated transcription factors (TFs), suggesting that mtDNA genes are separately regulated from the nucleus. However, several TFs, with known nuclear activities, were found to bind mtDNA and regulate mitochondrial transcription. Additionally, mtDNA transcriptional regulatory elements, which were proved important in vitro, were harbored by a deletion that normally segregated among healthy individuals. Hence, mtD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 58 publications
3
58
0
Order By: Relevance
“…To avoid statistical power issues, we focused our SNP association study on the most comprehensive list of human RNA-binding and transcription-associated mitochondrial genes available [16], supplemented by additional transcription factors that were recently localized to the human mitochondria and bind the mtDNA [18, 19]. This analysis showed 7,665 correlations between a total of 511 non-redundant nDNA SNPs and 15 mtDNA-encoded genes, of which only five SNPs in four nDNA-encoded genes remained significant after correction for multiple testing in both test groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid statistical power issues, we focused our SNP association study on the most comprehensive list of human RNA-binding and transcription-associated mitochondrial genes available [16], supplemented by additional transcription factors that were recently localized to the human mitochondria and bind the mtDNA [18, 19]. This analysis showed 7,665 correlations between a total of 511 non-redundant nDNA SNPs and 15 mtDNA-encoded genes, of which only five SNPs in four nDNA-encoded genes remained significant after correction for multiple testing in both test groups.…”
Section: Resultsmentioning
confidence: 99%
“…To identify possible associations of nDNA-encoded genes with differential expression patterns of mtDNA genes, the analysis focused on known SNPs (as listed by the 1000 Genomes Project) in the dataset of genes with known mitochondrial RNA-binding activity [16]. This dataset was supplemented by transcription factors and RNA-binding proteins that were recently identified in human mitochondria but were not included in MitoCarta (i.e., c-Jun, JunD, CEBPb, Mef2D) [18, 19]. Such prioritization was employed to enable detection of possible correlations with sufficient statistical power.…”
Section: Methodsmentioning
confidence: 99%
“…While rORX-B increased mitofusion, as indicated by the upregulation of MFN2, OPA1, and OMA1 gene expression, rORX-A promoted mitofission as reflected in the increased expression of MTFP1, DNM1, and MTFR1 genes. Despite the unchanged expression of TFAM (the direct regulator of mtDNA replication/transcription), the increased levels of mtDNA and CoxIV and Cox5a mRNA indicated that rORX-B might induce mitochondrial content and mass through other TFAM isoforms (22), TFAM posttranslational modifications (58), and/or other transcription factors (9). An increase in mitochondrial content following rORX-B treatment is also supported by the increased MitoTracker staining.…”
Section: Discussionmentioning
confidence: 97%
“…D‐loop binding has additionally been reported for the DNA methyltransferase Dnmt1, believed to play a role in reducing mtDNA transcript levels . Other non‐D‐loop binding nuclear transcription regulators were reported to influence mitochondrial transcription by directly binding on mitochondrial gene coding sequences, which included the myocyte enhancer factor 2D and the transcription factors c‐Jun, JunD, and CEBP …”
Section: Transcriptional Regulationmentioning
confidence: 95%